Answer:
A.
Step-by-step explanation:
The Elimination Method is the method for solving a pair of linear equations which reduces one equation to one that has only a single variable.
If the coefficients of one variable are opposites, you add the equations to eliminate a variable, and then solve.
If the coefficients are not opposites, then we multiply one or both equations by a number to create opposite coefficients, and then add the equations to eliminate a variable and solve.
When multiplying the equation by a coefficient, we multiply both sides of the equation (multiplying both sides of the equation by some nonzero number does not change the solution).
So, option B is not allowed (it is not allowed to multiply only one part of the equation)
Answer:2x-y-6=0 & 2x-y=6
Step-by-step explanation:
-3y=-6x+18.
-3y+6x=18
-y+2x=6
2x-y=6
2x-1y=6
2x-y=6
2x-y-6=0
Answer: A. The expression is not in a standard form because it isn't repersenting a y-value.
B. No the expression is not equivalent to (3-4), (2-2) because the correct expression should be written with 30−6x
Step-by-step explanation:
Sin^2 + cos^2 = 1
so,
(x/4)^2 + (y/4)^2 = 1
we got rid of t.